Fluctuation in ambient temperature: interplay between brown adipose tissue, metabolic health, and cardiovascular diseases - Tse-Yao Wang; Hua Zhou; Qinghua Sun (Wolters Kluwer Medknow Publications, 2016)
The variations in ambient temperature have been associated with high occurrence of cardiovascular diseases, which is one of the leading global risks for the mortality accounting for 50% of the death in the developed countries. Both heat- and cold-related excess mortalities are mostly attributable to the increase in cardiovascular diseases. Due to the loss of climate system balance caused by increased atmospheric concentration of greenhouse gases, the average global temperatures are expected to rise by 1.1-6.4°C from 1990 to the end of the 21st century. The reinforced intensity, duration, and frequency of heat waves were observed in the past decade with increased average atmosphere and ocean temperature on the Earth. The positive relationship between the heat wave and cardiovascular mortality and morbidity has been demonstrated in the areas with either lower or higher average temperatures. That is, to say, the sudden extreme heat condition lays stress on the cardiovascular system in humans. With a growing body of epidemiological studies, extreme temperature environments and cardiovascular conditions have been increasingly associated. As a class of chronic disorders, the initiation and development of cardiovascular diseases were mainly attributed to metabolic disorders reflecting the prolong stress from obesity, hypertension, hyperglycemia, and hypercholesterolemia whereas the stimulus of sudden temperature change was thought to trigger the onset or worsening of major cardiovascular diseases, which were established by these cumulative risk factors. However, the cold temperature exposure has recently been regarded as a novel therapeutic approach to defense against cardiovascular diseases such as obesity which is resulted from the imbalance between energy intake and energy expenditure. With the chronic mild reduction of ambient temperature, the prevalence and activity of brown adipose tissue (BAT) were upregulated, and the BAT-mediated thermogenesis helps the individual to correct the deviation of energy balance from excess white adipose tissue accumulations. The aim of the present paper was to systematically review the positive and negative effects of the ambient temperature change on cardiovascular diseases, which may lead to new intervention to metabolic health and cardiovascular disease prevention.